Melamine‐modified Boron‐doped Diamond towards Enhanced Detection of Adenine, Guanine and Caffeine. Issue 1 (23rd October 2015) - Niedziałkowski, P.; Bogdanowicz, R.; Zięba, P.; Wysocka, J.; Ryl, J.; Sobaszek, M.; Ossowski, T.
Abstract: This work describes the electrochemical method of boron‐doped diamond (BDD) modification by poly‐melamine to obtain organic films. The detection of adenine, guanine and caffeine was carried out by differential pulse wave voltammetry (DPV). The poly‐melamine modified B‐NCD electrodes exhibit excellent activity towards the electrochemical oxidation of all examined analytes. The poly‐melamine modified BDD electrodes in all measurements exhibit a larger peak current and are more sensitive compared to the unmodified BDD electrodes. The detection limit for adenine, guanine and caffeine using poly‐melamine modified BDD electrodes was found with 0.2 µM, 0.02 nM and 0.4 µM, respectively. Moreover, the double‐stranded (ctDNA), and single stranded DNA from calf thymus (ssDNA) was detected by DPV. Abstract :